An Analysis of Consumerism and Populism in the Film Air (2023) (Cinematology: Journal Anthology of Film and Television Studies, 2025)
The film Air (2023), directed by Ben Affleck, depicts the negotiations between Nike and basketball star Michael Jordan in creating the Air Jordan shoe line. This study analyzes how the film represents and reproduces capitalist ideologies through narrative and symbolic visualization of products. Employing a qualitative approach and media text analysis, the research utilizes Karl Marx's theory of commodity fetishism and John Storey's theory of popular culture to dissect the relationship between products, consumerism, and identity. The analysis reveals that Air not only documents the historical process of creating a cultural icon but also asserts the media's role in creating symbolic meanings of products as forms of lifestyle and social status. Through product personification, celebrity cultism, and the alignment of individual values with commodities, the film serves as a concrete example of how capitalism operates through cultural representation.